The cognitive adaptability and resiliency employment screener (CARES): tool development and testing - Torralba, Wilfredo Manuel R.; Savio, Marlyn Thomas; Huang, Xieyining; Manchanda, Priyanka; Steiger, Miriah; Bharucha, Timir; López, María Martín; Joyner, Keanan J.; Guevara, Rachel Lutz (Frontiers in Psychiatry, 2023)
Introduction To decrease psychological risk for content moderators, the study initiated the first steps of developing a robust employment screening tool, namely, the Cognitive Adaptability and Resiliency Employment Screener. Method The study consisted of three phases with 4,839 total participants. Results In Phase 1, a set of 75 items were developed and tested via exploratory factor analysis, yielding three factors (i.e., Psychological Perseverance & Agility, Rumination & Emotional Lingering, and Expressiveness & Sociability) and also reducing the scale to 67 items. In Phase 2 through confirmatory factor analysis, the three-factor structure showed good fit (CFI = .93, RMSEA = .05) and demonstrated sufficient overall reliability. In Phase 3, the convergent validity and divergent validity of the tool were established relative to constructs such as resilience, cognitive control and flexibility, emotion regulation, and optimism. Discussion Altogether, the findings revealed that the scale demonstrated good psychometric properties that, pending future studies, may serve as a promising employment screener for content moderators.